2003
DOI: 10.2105/ajph.93.8.1321
|View full text |Cite
|
Sign up to set email alerts
|

Nondaily Smokers: Who Are They?

Abstract: SD smokers make up a substantial segment of the smoking population. They are not just beginning to smoke nor trying to quit. Many have developed a long-standing pattern of nondaily smoking, smoking relatively few cigarettes on the days when they do smoke. They are not substantially younger than daily smokers, as one might expect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
161
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 13 publications
20
161
1
1
Order By: Relevance
“…The proportion of ND smokers found in this study is somewhat similar to that found among the general adult population (10 to 19%) in other studies of occasional smoking. 8,10 As found in the literature, 14 former ND smokers and NDND smokers differed in some important respects. NDND smokers consumed fewer cigarettes, were younger than 25 years old, and were more likely to have begun regular smoking after their teenage years.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The proportion of ND smokers found in this study is somewhat similar to that found among the general adult population (10 to 19%) in other studies of occasional smoking. 8,10 As found in the literature, 14 former ND smokers and NDND smokers differed in some important respects. NDND smokers consumed fewer cigarettes, were younger than 25 years old, and were more likely to have begun regular smoking after their teenage years.…”
Section: Discussionmentioning
confidence: 74%
“…9 Studies from the United States consistently show that ND or occasional smokers are more likely to be of a younger age, Hispanic, black, better educated, and more likely to want to quit smoking than the reference populations. 6,10,11 ND smokers are also more likely to have smoke-free workplaces and live in smoke-free homes. 12 It has also been suggested that ND smokers may not represent a homogenous group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nondaily smokers are more likely to be ethnic minority group members (Hassmiller et al, 2003;Tong et al, 2006;Wortley, Husten, Trosclair, Chrismon, & Pederson, 2003), making it important to aim for ethnically diverse samples in research on nondaily smoking.…”
mentioning
confidence: 99%